2004
DOI: 10.5694/j.1326-5377.2004.tb06157.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of complaints lodged by patients attending Victorian hospitals, 1997–2001

Abstract: Objective: To describe complaints by patients and compare rates of complaint in demographic subgroups of patients and hospital departments. Design and setting: Retrospective analysis of complaints made by patients attending 67 hospitals (metropolitan, 25; rural, 42) in Victoria, and lodged with the Victorian Health Complaint Information Program (January 1997 – December 2001). Main outcome measures: Demographic characteristics of patients lodging complaints and the hospital department involved; nature and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 17 publications
1
60
1
2
Order By: Relevance
“…Cooke et al 10 demonstrated that over 90% of patients who visit the ED expect explanations of test results and the reasons for the tests. Poor communication has been shown to be the most common reason for complaints11 and is a frequent factor in the aetiology of patient safety incidents 12. Interventions to improve communication with patients have been shown to improve patient satisfaction in the ED 13.…”
Section: Discussionmentioning
confidence: 99%
“…Cooke et al 10 demonstrated that over 90% of patients who visit the ED expect explanations of test results and the reasons for the tests. Poor communication has been shown to be the most common reason for complaints11 and is a frequent factor in the aetiology of patient safety incidents 12. Interventions to improve communication with patients have been shown to improve patient satisfaction in the ED 13.…”
Section: Discussionmentioning
confidence: 99%
“…For example, students encounter poor role models in their clinical studies [9, 10] or clinical teachers do not feel prepared to take on the role of supervisors in professional competencies [3]. And physicians’ professional competence, or rather the lack of it, is high on the patients’ complaints lists [11]. Furthermore, although professional competence is seen as important in the process of educating medical doctors in the best possible way, it still seems to decline during medical education [9, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Managing the expectations of these patients and their families becomes even more challenging in an environment where many actions are time dependent. [35]…”
Section: Introductionmentioning
confidence: 99%